"Light modulates transcriptomic dynamics upregulating astaxanthin accumulation in Haematococcus: A review". (November 2021) - Ahirwar, Ankesh; Meignen, Gurvan; Jahir Khan, Mohd.; Sirotiya, Vandana; Harish,; Scarsini, Matteo; Roux, Sylvain; Marchand, Justine; Schoefs, Benoît; Vinayak, Vandana
Highlights: Haematococcus pluvialis accumulates Bioastaxanthin under stress. High Light intensity or red/blue light acts as stress inducers. Transcriptomic study locates the upregulated genes for astaxanthin synthesis. Enormous impact on Circular Bioeconomy if cost of harvest is decreased. Abstract: Haematococcus pluvialis is a green alga that can accumulate high astaxanthin content, a commercially demanding market keto food. Due to its high predicted market value of about 3.4 billion USD in 2027, it is essential to increase its production. Therefore, it is crucial to understand the genetic mechanism and gene expressions profile during astaxanthin synthesis. The effect of poly- and mono-chromatic light of different wavelengths and different intensities have shown to influence the gene expression towards astaxanthin production. This includes transcriptomic gene analysis in H. pluvialis underneath different levels of illumination stress. This review has placed the most recent data on the effects of light on bioastaxanthin production in the context of previous studies, which were more focused on the biochemical and physiological sides. Doing so, it contributes to delineate new ways along the biotechnological process with the aim to increase bioastaxanthin production while decreasing production costs.